Development of a Novel Large Animal Model to Evaluate Human Dental Pulp Stem Cells for Articular Cartilage Treatment - Fernandes, Tiago Lazzaretti (Stem Cell Rev, 2018)
PURPOSE: Chondral lesion is a pathology with high prevalence, reaching as much as 63% of general population and 36% among athletes. The ability of human Dental Pulp Stem Cells (DPSCs) to differentiate into chondroblasts in vitro suggests that this stem cell type may be useful for tissue bioengineering. However, we have yet to identify a study of large animal models in which DPSCs were used to repair articular cartilage. Therefore, this study aimed to describe a novel treatment for cartilage lesion with DPSCs on a large animal model. METHODS: Mesenchymal stem cells (MSC) were obtained from deciduous teeth and characterized by flow cytometry. DPSCs were cultured and added to a collagen type I/III biomaterial composite scaffold. Brazilian miniature pig (BR-1) was used. A 6-mm diameter, full-thickness chondral defect was created in each posterior medial condyle. The defects were covered with scaffold alone or scaffold + DPSCs on the contralateral side. Animals were euthanized 6 weeks post-surgery. Cartilage defects were analyzed macroscopically and histology according to modified O’Driscoll scoring system. RESULTS: Flow cytometry confirmed characterization of DPSCs as MSCs. Macroscopic and histological findings suggested that this time period was reasonable for evaluating cartilage repair. To our knowledge, this study provides the first description of an animal model using DPSCs to study the differentiation of hyaline articular cartilage in vivo. CONCLUSION: The animals tolerated the procedure well and did not show clinical or histological rejection of the DPSCs, reinforcing the feasibility of this descriptive miniature pig model for pre-clinical studies.